2016
DOI: 10.1002/psp.2027
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Skilled and Less‐Skilled Interregional Migrations in China, 2000–2005

Abstract: Previous analysis and modelling of interregional migration in China have treated migrants as a homogenous group. The flow of skilled migration is the focus of recent research. However, the skilled and less-skilled migrations have not been systematically analysed and compared in terms of their determinants. Previous modelling of interregional migration in China does not take network autocorrelation into consideration. This paper attempts to fill this research gap by modelling skilled and less-skilled migrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 62 publications
6
84
1
Order By: Relevance
“…Migrants are a heterogeneous group with different levels of educational attainment, which may have significant impacts on settlement intentions. Consistent with previous studies on Chinese migrants (Chan, ; Liu & Shen, ), skilled migrants are those with a tertiary educational qualification, and less‐skilled migrants are those whose highest level of education is senior high school or lower. As discussed above, average wage levels in large first‐tier cities tend to be higher than those in smaller ones.…”
Section: Urban Economic (Dis)incentives Education and Migrants' Setsupporting
confidence: 85%
“…Migrants are a heterogeneous group with different levels of educational attainment, which may have significant impacts on settlement intentions. Consistent with previous studies on Chinese migrants (Chan, ; Liu & Shen, ), skilled migrants are those with a tertiary educational qualification, and less‐skilled migrants are those whose highest level of education is senior high school or lower. As discussed above, average wage levels in large first‐tier cities tend to be higher than those in smaller ones.…”
Section: Urban Economic (Dis)incentives Education and Migrants' Setsupporting
confidence: 85%
“…The third specification (Equation ) combines these two effects together. In recent studies, more researchers used the third specification to define network weight matrix, and they showed the improvement of considering the competing destination effects and the intervening opportunities effects simultaneously into a network model (e.g., Almeida & Gonçalves, ; Chun, ; Gu et al, ; Guldmann, ; Liu & Shen, ). In this research, we defined a network weight matrix using the third specification.…”
Section: Methodsmentioning
confidence: 99%
“…Using an ESF Poisson GM, Shen () modelled the determinants of interprovincial migration in China from 2005 to 2010, and Shen employed an error analysis based on this model to see which factors of the migration process could make the model more accurate. Extending the ESF Poisson migration model to the ESF negative binomial migration model, Liu and Shen () examined the determinants of skilled and less skilled interprovincial migration in China, and they found that distance, unemployment rate, and foreign direct investment affected skilled worker migration moderately, but wages had a greater effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent years have witnessed the combination of the gravity model and the spatial OD model (or ESF) in several empirical studies on determinants of China's interprovincial migration, whereas such spatial models have not been applied in topics on interregional migration intentions. Using the ESF negative binomial regression model, Liu and Shen () examined the determinants of skilled and less skilled interprovincial migration in China and found that skilled migrants were less influenced by factors such as distance and unemployment rate compared with less skilled migrants. Besides, Pu, Han, Ge, and Kong () built the spatial OD model of interprovincial migration flows on the basis of the sixth national population census data of China and concluded that the multilateral effects of the regional economic and social factors through the spatial network system led to the clustering migration flows across interrelated regions.…”
Section: Literature Reviewmentioning
confidence: 99%